(3GdJfbjH Ydi eG aj GdebGeGJ ef GdZQjH (B-(3ebGeGJ GdMQjQjs - (3CHi YHO Gddg eMeO Hf YHO Gddg Hf eMeO Hf XaQ GdUbdjs; (3GHf XaQ,J (B565 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf GdYde CQaY fSH hCfaY ecJSH hEf JCKjQ GdYdeGA ai GdCfGe cJCKjQ GdCdHGH ai GdCLSGe deG YGjfhg ef ENdGO GdfahS Edi CMdGe GdOYI hYGO EMSGSgG HBdGe GdVYI cGdPi VYg s
(3BNQgG (B:s
(3hGSJhba Gddg dCed JhLg EdjfG bhGg hCYhP Hg ef Yed de jeSc Ydi JbhGg agh MSHfG hfYe Gdhcjd GdMeO ddg Ydi CefjI COfGgG aHdZgG hfYeI SfjI SfGgG aShZgG s
(3GdfSNI HgG MhGTs
(3HgG JYdjbGJ hebGHdGJs
(3HgG fbU ef hQbI (B75-79s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs